A Collaboratively Hidden Location Privacy Scheme for VANETs. (24th March 2014) - Mei, Ying; Jiang, Guozhou; Zhang, Wei; Cui, Yongquan
Communication messages in vehicular ad hoc networks (VANETs) can be used to locate and track vehicles, and this can lead to threats on location privacy of vehicle users. In this paper, we address the problem of privacy and liability in VANETs. We propose a scheme that provides location privacy by utilizing a variant of ring signature. It allows a vehicle to form a ring arbitrarily with nearby vehicles and sign its messages anonymously, so that it can hide itself in the surrounding vehicles. When solving a dispute, the real signer will be responsible for what it has signed as the anonymity is revocable by the authority.